Less Might Be More: Conduction Failure as a Factor Possibly Limiting the Efficacy of Higher Frequencies in rTMS Protocols - Halawa, Islam; Goldental, Amir; Shirota, Yuichiro; Kanter, Ido; Paulus, Walter (Frontiers in Neuroscience, 2018)
Introduction: rTMS has been proven effective in the treatment of neuropsychiatric conditions, with class A (definite efficacy) evidence for treatment of depression and pain (Lefaucheur et al 2014) (1). The efficacy in stimulation protocols is, however, quite heterogeneous. Saturation of neuronal firing by HFrTMS without allowing time for recovery may lead to neuronal response failures (NRFs) that compromise the efficacy of stimulation with higher frequencies Objectives: To examine the efficacy of different rTMS temporal stimulation patterns focusing on a possible upper stimulation limit related to response failures. Protocol patterns were derived from published clinical studies on therapeutic rTMS for depression and pain. They were compared with conduction failures in cell cultures. Methodology: From 57 papers using protocols rated class A for depression and pain (Lefaucheur et al., 2014) we extracted Inter-train interval (ITI), average frequency, total duration and total number of pulses and plotted them against the percent improvement on the outcome scale. Specifically, we compared 10 Hz trains with ITIs of 8 seconds (protocol A) and 26 seconds (protocol B) in vitro on cultured cortical neurons. Results: In the in vitro experiments, protocol A with eight-second ITIs resulted in more frequent response failures, while practically no response failures occurred with protocol B (26-second intervals). The HFrTMS protocol analysis revealed that an ITI < 20 seconds was less effective than a longer ITI. Discussion: Longer ITIs appeared to allow the neuronal response to recover. In the available human dataset on both depression and chronic pain, ITIs shorter than 20 seconds exhibited a significantly lower efficacy compared to those longer than 20 seconds did. Significance: NRF may interfere with the efficacy of rTMS stimulation protocols when the average stimulation frequency is too high.